2016
DOI: 10.1007/s00259-016-3431-4
|View full text |Cite
|
Sign up to set email alerts
|

The reoxygenation of hypoxia and the reduction of glucose metabolism in head and neck cancer by fractionated radiotherapy with intensity-modulated radiation therapy

Abstract: Both the intensity and the volume of tumor hypoxia rapidly decreased in the early phase of radiotherapy, indicating reoxygenation of the tumor hypoxia. In contrast, the FDG uptake declined gradually with the course of radiotherapy, indicating that the tumoricidal effect continues over the entire course of radiation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Our tumour SUVmax values appeared higher than those obtained by Havelund et al [ 44 ] who imaged rectal tumours with [ 18 F]FAZA PET at 2 h. Tumour hypoxic volumes obtained in this study were difficult to compare with those shown by Roels et al [ 42 ], who based rectal tumour ROI on [ 18 F]FDG PET. Our T:M ratio values are however similar to those obtained in other solid tumour types such as head and neck squamous cell carcinoma [ 45 48 ] and non-small cell lung cancer [ 49 ]. Where quoted, hypoxic tumour fraction appeared higher in these tumours than in rectal cancer [ 48 , 50 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our tumour SUVmax values appeared higher than those obtained by Havelund et al [ 44 ] who imaged rectal tumours with [ 18 F]FAZA PET at 2 h. Tumour hypoxic volumes obtained in this study were difficult to compare with those shown by Roels et al [ 42 ], who based rectal tumour ROI on [ 18 F]FDG PET. Our T:M ratio values are however similar to those obtained in other solid tumour types such as head and neck squamous cell carcinoma [ 45 48 ] and non-small cell lung cancer [ 49 ]. Where quoted, hypoxic tumour fraction appeared higher in these tumours than in rectal cancer [ 48 , 50 ].…”
Section: Discussionsupporting
confidence: 87%
“…Hypoxic regions in tumours are known to be more radiation-resistant than normoxic tissues and hypoxia is an independent prognostic marker for patient outcome [15]. Most head-and-neck cancers have hypoxic regions, which vanish in the course of radiation therapy [6]. The current gold standard to estimate hypoxic tissue is measuring the pO2 using the Eppendorf pO2 electrode [7], which not only is an invasive method but also can alter the local oxygen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that HDR induces reoxygenation in the hypoxic area in the poor-circulated solid tumor (Hong et al, 2016;Moon et al, 2010;Okamoto et al, 2016). The respiratory system in humans is co-developed with the cardiovascular system via crosstalk and integration of multiple cellular populations (Morrisey and Hogan, 2010).…”
Section: Improving Alveolar Gas Exchange By Hdr-induced Vasculature Mmentioning
confidence: 99%